Mycotic keratitis due to Scedosporium apiospermum in layer pullets. (28th May 2013) - McCowan, Christina; Bibby, Susan; Scott, Peter C.
Abstract Investigation of ocular disease in a flock of layer pullets identified corneal infection with Scedosporium apiospermum, a fungus of emerging significance in medicine and veterinary medicine.